Noire géline pond blanc œuf ou Poules et poulaillers médiévaux - Perrine Mane (Revue d'ethnoécologie)
In the medieval iconography, the documents which represent hens and henhouses are many and varied. They underline the importance of the poultry and of the eggs in the food balance of the population and give evidence of the significant role held by gallinaceans not only in the life of rural areas but also in the urban economy which is rapidly expanding.